RESPON MAHASISWA PERBANKAN SYARI’AH TERHADAP PENDIRIAN GALERI INVESTASI BURSA EFEK INDONESIA SEKOLAH TINGGI AGAMA ISLAM NEGERI PAMEKASAN - Lely Shofa Imama (Research Institute and Community Engagement of IAIN MADURA, 2015)
BEI Investment gallery STAIN Pamekasan as a realization of capital market laboratory will always engage academician, especially Perbankan Syari’ah students, as the object of the investment gallery. This research is field research employing descriptive quantitative method. Its objective is to identify the level of knowledge and response toward the existence of BEI Investment gallery in STAIN Pamekasan. The result shows that students of Syariah Banking Program just simply know, whereas they absolutely agree with the urgency of laboratory capital market and the founding of BEI investment gallery STAIN Pamekasan.